Factors influencing the behaviour and perceptions of Australian veterinarians towards antibiotic use and antimicrobial resistance - Norris, Jacqueline M. (PLoS One, 2019)
Antimicrobial resistance (AMR) is a global crisis with impacts on the future health and welfare of humans and animals. Determining key factors that influence veterinarians’ antimicrobial prescribing behaviours can bridge the gap between prescribing guidelines and clinical usage. Veterinarians practicing in Australia were surveyed on their frequency in prescribing different antibiotics; factors influencing their antibiotic prescribing behaviours; and their perceptions of current drivers of AMR. Antibiotics were prescribed in a third of consultations with key differences in the frequency of use of specific antibiotics by small companion animal (SCA), equine and livestock veterinarians, which broadly aligned with antibiotic registration restrictions in Australia. SCA veterinarians reported prescribing broad-spectrum antibiotics of higher importance to human health more frequently than livestock veterinarians. Factors that were reported as ‘strong’ or ‘moderate’ barriers to appropriate antibiotic prescribing were the 1) cost of culture and susceptibility testing and 2) lack of access to rapid and affordable diagnostic tests. Fear of losing clients, colleague pressure, and lack of their own understanding about antibiotics were considered to be ‘no’ or ‘somewhat’ of a barrier to appropriate prescribing by respondents. SCA veterinarians placed greater importance on the contribution of antibiotic use in livestock to AMR, than antibiotic use in companion animals. Despite reporting use of fewer, mostly narrow spectrum antibiotics of lower importance to human and animal health, livestock veterinarians were generally more aware of their potential contribution to AMR. This study provides insights into the similarities and differences in SCA, equine and livestock veterinarians practicing in Australia and informs sector-specific strategies to improve antimicrobial stewardship.